Correspondence between cortical tau and atrophy in aged non‐demented adults with Down syndrome. (December 2021) - Taylor, Lisa; Doran, Eric; Poline, Jean‐Baptiste; Nguyen, Dana; Krinsky‐McHale, Sharon J.; Price, Julie C.; Sathishkumar, Mithra; Kreisl, William Charles; Hom, Christy; Pulsifer, Margaret; Lai, Florence; Rosas, H. Diana; et al.
Abstract: Background: Individuals with Down syndrome (DS) have a higher likelihood of developing early‐onset Alzheimer's disease which has been associated with abnormal tau proteins and atrophy in the brain [1]. Prior research has shown a spatial relationship between tau and atrophy in neurotypicals with dementia [2]. Although tau and atrophy certainly contribute independently to dementia, the synergistic relationship in a non‐demented population with DS is not well understood. This study aims to identify cortical regions with high tau and atrophy in aged, non‐demented participants with DS. Method: Analysis included 28 non‐demented participants (49.8 +/‐ 6.4 years; 17 males) with DS from the Alzheimer's Disease in Down Syndrome (ADDS) study. Tau PET ( 18 F‐AV1451) and MRI scans were acquired within the same timeframe (1.8 months +/‐1.5). Gray‐matter cortical ribbons were extracted from T1 MRI segmentations with Freesurfer (RRID: SCR_001847). The cortical ribbons were used to mask the coregistered PET scan data and converted to standard uptake value ratio (SUVR) units using the cerebellar cortex reference region. The tau and gray‐matter images were converted to z‐score images using the group mean and standard deviation. We defined high tau as voxels with z‐scores >=2.0 and high atrophy as voxels with gray matter z‐scores <= ‐2.0. The z‐score images were spatially normalized into MNI space with ANTs (RRID: SCR_004757) and a voxel‐based correspondence analysis was performed. Voxels surviving the high tau and high atrophy thresholds were evaluated to determine anatomical localization using the Desikan/Killiany atlas [3]. Result: We found high correspondence between tau and atrophy in the following regions (figure 1): entorhinal cortex, insula, fusiform, pars orbitalis, paracentral, precentral, superior temporal, medial orbitofrontal, lateral orbitofrontal, temporal pole, rostral middle frontal, superior frontal, pars triangularis, lingual, and the amygdala. Conclusion: Our study demonstrated a correspondence between atrophy and tau in deep cortical structures, as well as frontotemporal regions in aged, non‐demented adults with DS. Many of these regions are consistent with findings in neurotypical populations and shown in our prior work to be regions associated with increased amyloid ( 18 F‐AV‐45) as a function of disease severity in DS [4].